Development of Cobalt-Doped Nickel Hydroxide Sol-Gel Catalysts for Enhanced Electro-Oxidation of Urea - Tatarchuk, Stephen William (University of Waterloo, 2021)
Electrochemical oxidation of urea provides an approach to prevent excess urea emissions into the environment while generating value by capturing chemical energy from waste. Unfortunately, the source of high catalytic activity in state-of-the-art doped nickel catalysts for urea oxidation reaction (UOR) activity remains poorly understood, hindering the rational design of new catalyst materials. In particular, the exact role of cobalt as a dopant in Ni(OH)2 to maximize the intrinsic activity towards UOR remains unclear. This thesis explores how tuning the Ni:Co ratio in a modified propylene oxide synthesis of Ni1-xCox(OH)2 xerogel catalysts alters both structural and electronic states which allows one to tune the number and intrinsic activity of redox-active surface sites towards UOR. For the Ni1-xCox(OH)2 catalysts studied, Ni90Co10 (OH)2 achieves the largest geometric current density due to the increase of available surface sites and that intrinsic activity towards UOR is maximized with Ni20Co80(OH)2. Through density functional theory calculations, we show that the introduction of Co alters the Ni 3d electronic state density distribution to lower the minimum energy required to oxidize Ni and influence potential surface adsorbate interactions.
Keywords: urea oxidation reaction; electronic structure; nickel-cobalt hydroxide; electrocatalysis; DFT; sol-gel